Efektivitas elektroakupunktur pada GV 20 dan EX-HN 3 terhadap penurunan gejala gangguan depresi mayor - Chantika Mahadini; Leny Candra Kurniawan; Ikhwan Abdullah (Holistik Jurnal Kesehatan, 2026)
Background: Major Depressive Disorder (MDD) is a mental health condition with a high prevalence that significantly impacts patients’ quality of life. Although pharmacological therapy is the primary treatment option, its effectiveness is often limited by slow clinical response, medication side effects, and low patient adherence. Electroacupuncture at points GV 20 (Baihui) and EX-HN 3 (Yintang) offers a potential complementary intervention through neurobiological stimulation to regulate neurotransmitters and brain activity. Purpose: To analyze the effectiveness of electroacupuncture therapy at points GV 20 and EX-HN 3 in reducing symptom severity in patients with major depressive disorder. Method: This quantitative study employed a quasi-experimental design using a one-group pretest–posttest approach and was conducted from April to May 2026 at Rumah Tabinda in Malang. The sampling technique used was purposive sampling, with a sample size of 30 respondents. The independent variable in this study was electroacupuncture therapy at the GV20 and EX-HN3 acupoints, while the dependent variable was the reduction in the severity of depressive symptoms. Data analysis included univariate analysis in the form of frequency distributions and bivariate analysis using a paired-sample t-test. Results: Measurements of depression levels showed a decrease in the mean HAMD score from 22.37 ± 3.92 at the pretest to 15.85 ± 2.37 at the posttest. Statistical analysis revealed p=0.000 (p<0.05), demonstrating a significant effect of the intervention on reducing the respondents’ depression levels. Conclusion: Electroacupuncture therapy at the GV20 (Baihui) and EX-HN3 (Yintang) acupoints is effective in reducing the severity of depression in patients with Major Depressive Disorder.   Keywords: Electroacupuncture; EX-HN3; GV20; Hamilton Depression Rating Scale; Major Depressive Disorder.